The Integration of the Two Key Levers for the Success of a Company - Derradji, Rima; Hamzi, Rachida (1st Conference of the Arabian Journal of Geoscience (CAJG).Paper n° 650, 2018)
Most managers know that process-risk mapping is essential in enterprise design so as to obtain better understanding and management practices. Organizations need an effective and robust process of management that is less sensitive to changes in the business environment. The main purpose of this paper is the integration of process mapping and risk mapping, with a case study applied in an Algerian company in the oil and gas industry.